On certain real hypersurfaces of quaternionic projective space - Juan De Dios Perez; Florentino G. Santos (International Journal of Mathematics and Mathematical Sciences)
We classify certain real hypersurfaces ot a quaternionic projective space satisfying the condition σ(R(X,Y)SZ)=0.